Thomas & friends. Sticky situations [videorecording (DVD)] - Tiernan, Greg; Brandon, Michael, 1945-; Sherman, Martin T.; Bedella, David, 1962- (Hit Entertainment ; distributed by] Lionsgate, 2012)
The engines on the Island of Sodor find themselves in some sticky and slippery situations. Thomas and Butch are stuck in a bind when they don't fully listen to directions. Spencer gets lost in the fog but learns he can actually be Spencer the Helpful. Gordon must swallow his pride after dropping the Lion of Sodor in the mucky, muddy river, and Edward shows Charlie there's a time to be really fun and a time to be really useful.